Chemical Properties of Inland Peat in Horticultural Crops and Oil Palm Plantation, Central Kalimantan - Silalahi, Artha Theresia; Yulianti, Nina; Jaya, Adi; Damanik, Zafrullah; Darung, Untung (JURNAL AGRIMENT, 2024)
The purpose of the study was to determine the differences in soil chemical properties in horticultural crops and oil palm plantations in Central Kalimantan. The research was conducted in Kalampangan (horticulture) and Tumbang Nusa (oil palm) using quantitative analysis. Soil samples were taken at a depth of 0-30 cm with a soil drill, and data were analyzed by regression and correlation using Microsoft Excel 2022 presented in tables and graphs. The results showed that the chemical properties of peat in the mustard field were classified as low with a pH of 3,98 (very acidic), C-organic content of 53,5% (very high), ash content of 6,3% (low) and moisture content of 159.56% (high). The chemical properties of the peat in the corn field were low with a pH of 3,84 (very acidic), a C-organic content of 54,1% (very high), an ash content of 5.5% (low) and a moisture content of 216,04% (high). The chemical properties of the peat on the oil palm land were low with a pH of 3,41 (very acidic), a C-organic content of 57,5% (very high), an ash content of 0.8% (low) and a moisture content of 242,07% (high). Based on the results of the Correlation Test at the Kalampangan and Tumbang Nusa locations, it was found that there was no difference in the strength of the relationship between variables in both Kalampangan and Tumbang Nusa. Regression test results show that the relationship between C-organic and ash content is negative (opposite). The relationship between C-organic and moisture content is positive (unidirectional). The relationship between C-organic and soil pH is negative (opposite). The relationship between pH and ash content is positive (unidirectional). The relationship between pH and water content is negative (opposite). The relationship between water content and ash content is negative (opposite). The results of the T test on soil pH, C-organic and ash content showed that there was a significant difference between horticultural crops and oil palm plantations, while the results of the T test on soil water content showed that there was no significant difference between horticultural crops and oil palm plantations.